2014
DOI: 10.1016/j.pjnns.2014.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Small volume of the posterior cranial fossa and arterial hypertension are risk factors of hemifacial spasm

Abstract: There was no significant difference in VPCF and in frequency of AH diagnosis in HFS patients and age- and sex-related controls, but the logistic regression analysis showed that small VPCF and AH duration are risk factors of HFS in younger and older patients respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In addition, in patients with hypertension but no HFS, we also need to consider that HFS may develop. Although hypertension is not a clear risk factor for HFS, a study by Rudzinska et al found that an increased duration of arterial hypertension was a significant risk factor for HFS, suggesting a possible etiologic link 11 . Perren F et al 12 found a relationship between hemodynamic changes in the vessels most frequently associated with HFS and the side of the HFS and arterial hypertension, was found in 58% of their patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in patients with hypertension but no HFS, we also need to consider that HFS may develop. Although hypertension is not a clear risk factor for HFS, a study by Rudzinska et al found that an increased duration of arterial hypertension was a significant risk factor for HFS, suggesting a possible etiologic link 11 . Perren F et al 12 found a relationship between hemodynamic changes in the vessels most frequently associated with HFS and the side of the HFS and arterial hypertension, was found in 58% of their patients.…”
Section: Discussionmentioning
confidence: 99%
“…While publication bias may arise from only using publicly available data, we ensured that we screened through all the abstracts, even those from journals which were not publicly available, and found that none of these studies were relevant to our topic. 2 papers 11 18 were subsequently further excluded since their measure of hypertension was indirect. Hence, data from 6 papers were eventually pooled together and analysed.…”
Section: Methodsmentioning
confidence: 99%
“…Patients with HFS suffer from facial muscle spasms which can impact social interaction with others and their quality of life 1) . The most common cause of HFS is a neurovascular conflict between the artery and the facial nerve at the root entry zone of the brainstem 13) .…”
Section: Introductionmentioning
confidence: 99%